Women Fisherman Empowerment Based on Local Potential in Sidoarjo: Social Entrepreneurship Approach - Didiek Tranggono; Jojok Dwiridhotjahjono; Sonja Andarini; Resa Rasyidah (Future Science)
Women fishermen are one of the social groups in the community who fall into the category below poverty. Poverty is caused by complex factors that are interconnected and are the main sources that weaken the ability of the community in building the region and improve its welfare. Therefore, poverty is one of the main issues in the development of coastal areas, especially the group of women fishermen. Model of empowerment of local fishermen-based women in Sidoarjo Regency using social entrepreneurship approach combined with participatory approach is an effort to develop independence and prosperity of fishermen women by increasing knowledge, attitude, skill, behavior, ability, awareness, and resource utilization and the optimization of local potential through the establishment of policies, programs, activities and assistance in accordance with the essence of the problems and priorities of fulfilling basic needs through the development of local economic potential by taking into account the sustainability of the environment in an integrated manner.